A institucionalidade da ciência, tecnologia e inovação na Amazônia e a conformação de trajetórias e paradigmas tecnológicos - MONTEIRO, Maurílio de Abreu (2012)
Analyzes aspects of production and appropriation of science and technology in the Brazilian Amazon and their relation with development strategies. Based on statistical indicators, were analyzed the links between the scientifi c production and regional commodity production, the dimension of this production, the quality of institutions of science, technology and innovation in the region, and its degree of specialization and densifi cation. The article indicates that the observed patterns create blockages to the consolidation of trajectories and technological paradigms are necessary to drive the dynamics of sustainable development in the region.